020 Pre-hospital dressings use in soft tissue trauma—is there any conformity or plan. Issue 3 (1st March 2011) - Jones, Alex; Allison, K; Wright, H; Porter, K
Abstract : Background: Acute soft tissue wounds are commonly seen in the pre-hospital setting.We hypothesised that there is a lack of consistency in early trauma wound management, particularly in terms of dressings used. Methods: In January 2007, we undertook a questionnaire-based study to evaluate the early management of such injuries. All thirteen UK ambulance services were contacted. In addition two voluntary ambulance services were also contacted. The questionnaire considered the following aspects: Implementation of a wound treatment policy and staff training, immediate wound management including haemostasis, cleansing, analgesia, dressings and the use of antibiotics. Results: The response rate was 100%. Only 27% of services had a wound treatment policy in place, but all services implemented staff training. All services regularly achieved haemostasis of wounds using a combination of pressure and elevation. Regular cleansing was performed by 47% of services and those that did so used normal saline or water. All ambulance services administered analgesics. The most commonly used analgesics were Entonox and intravenous (IV) morphine. Other analgesics administered were Paracetamol and Ibuprofen. No local anaesthesia was utilised. Dressings were applied regularly by all services. Thirteen different types of dressings were in regular use. Conclusions: This study has confirmed that at present there is no national standard protocol for early acute wound management in the pre-hospital care setting. The key areas for improvement are cleansing, dressing simplification and introduction of standardised protocols and teaching.